Lithium isotopic systematics of submarine vent fluids from arc and back‐arc hydrothermal systems in the western Pacific. (1st October 2016) - Araoka, Daisuke; Nishio, Yoshiro; Gamo, Toshitaka; Yamaoka, Kyoko; Kawahata, Hodaka
Abstract: The Li concentration and isotopic composition (δ 7 Li) in submarine vent fluids are important for oceanic Li budget and potentially useful for investigating hydrothermal systems deep under the seafloor because hydrothermal vent fluids are highly enriched in Li relative to seawater. Although Li isotopic geochemistry has been studied at mid‐ocean‐ridge (MOR) hydrothermal sites, in arc and back‐arc settings Li isotopic composition has not been systematically investigated. Here we determined the δ 7 Li and 87 Sr/ 86 Sr values of 11 end‐member fluids from 5 arc and back‐arc hydrothermal systems in the western Pacific and examined Li behavior during high‐temperature water‐rock interactions in different geological settings. In sediment‐starved hydrothermal systems (Manus Basin, Izu‐Bonin Arc, Mariana Trough, and North Fiji Basin), the Li concentrations (0.23–1.30 mmol/kg) and δ 7 Li values (+4.3‰ to +7.2‰) of the end‐member fluids are explained mainly by dissolution‐precipitation model during high‐temperature seawater‐rock interactions at steady state. Low Li concentrations are attributable to temperature‐related apportioning of Li in rock into the fluid phase and phase separation process. Small variation in Li among MOR sites is probably caused by low‐temperature alteration process by diffusive hydrothermal fluids under the seafloor. In contrast, the highest Li concentrations (3.40–5.98 mmol/kg) and lowest δ 7 Li values (+1.6‰ to +2.4‰) of end‐member fluids from the Okinawa Trough demonstrate that the Li is predominantly derived from marine sediments. The variation of Li in sediment‐hosted sites can be explained by the differences in degree of hydrothermal fluid‐sediment interactions associated with the thickness of the marine sediment overlying these hydrothermal sites. Key Points: First Li isotopic report on submarine vent fluids from arc and back‐arc hydrothermal systems Li in vent fluids can be explained mainly by dissolution‐precipitation model during seawater‐rock and seawater‐sediment interactions Variation in Li due to diffusive hydrothermal fluid and the degree of hydrothermal fluid‐sediment interaction